Drug eruption: A mimicker of Coronavirus disease-2019 rash - Tülin Ergun; Ilkay Ergenç; Seda Seven; Dilek Seçkin; Elif Cömert Özer; Meryem Aktaş; Elif Tükenmez Tigen (Galenos Publishing House, 2022)
Severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infections can be associated with several cutaneous lesions, among which maculopapular rash is the most common. A maculopapular rash can also be induced by medications used for Coronavirus disease-2019 (COVID-19) treatment. The distinction between viral rash and drug eruption may be difficult especially in case of several medication use for COVID-19. Thus, this study aimed to describe cutaneous manifestations in six patients with COVID-19 and highlight clues for distinguishing SARS-CoV-2-related rash and drug eruption. Between March and June 2020, 1,492 patients were hospitalized for COVID-19 and treated with hydroxychloroquine in Marmara University Hospital. Among them, six cases were consulted for possible COVID-19-related rash or drug reaction. Hydroxychloroquine was given as monotherapy in one patient. All six patients developed an erythematous, symmetrical, and maculopapular eruption that mainly affected the trunk, axilla, and genitocrural region, 5-21 days after the onset of COVID-19 symptoms. Five patients developed rash in 4-11 days after treatment completion. Pruritus was severe. All were treated with topical corticosteroids and oral antihistamines, which provided partial relief. The resolution of the eruption was typically slow, which took a few weeks. A long period between the COVID-19 symptoms and the eruption, as well as slow recovery, is in favor of drug eruption. The effects of co-existent viral infection, a well-known promoting drug eruption factor, in facilitating adverse drug reaction in patients with COVID-19 needs further observations and research.